CSDP on the brink: The importance of bringing France and the United Kingdom back in - Ronja Kempin; Nicolai von Ondarza (Stiftung Wissenschaft und Politik (SWP), 2011)
The Lisbon reforms were aimed in particular at making the EU a more coherent and capable foreign policy player. Yet, in the face of the upheavals in its southern neighborhood, the EU and its Member States have not succeeded in crafting a common response nor have they jointly addressed the resulting challenges. To the contrary: in responding to the conflict in Libya, EU Member States have publicly taken opposing positions, bypassed High Representative Ashton and plunged the EU into another crisis. To prevent the ongoing erosion of the Union's security and defense policy, decisive policy measures are urgently needed. Here, the cooperation of Germany, France, and the United Kingdom will play a key role. Paris and London will only agree to strengthen the EU framework, however, if policy makers in Berlin are willing to make a substantial contribution to the military dimension of the CSDP
Keywords: 350